Uropathogen antibiogram regional variations—Are Australian antimicrobial guidelines appropriate? - Gavin Wei; James Antony Sidney Sewell; Caroline Bartolo; Amelia Pearce; Owen Harris; Richard Grills (BJUI Compass)
Abstract Objectives The objectives of this study are as follows: to assess the uropathogen antibiogram at two tertiary hospitals in Victoria to look at the difference in susceptibility patterns, to assess whether national guideline recommendations were applicable and to assess the feasibility of local antibiogram analysis to guide development of hospital‐specific guidelines for empirical treatment of urosepsis and for pre‐operative prophylaxis for urological procedures. Patients and methods All positive urine cultures analysed at Barwon Health and Monash Health, two tertiary hospitals in regional and metropolitan Victoria, Australia, respectively, between January 2019 and December 2020 were retrospectively identified. Data obtained included the organism cultured and their susceptibility profiles. Results Three thousand seven hundred and seventy‐seven positive urine cultures from Barwon Health and 6821 from Monash Health were identified. The most common uropathogen was Escherichia coli, which was cultured in 53.4% and 59.1% of urine cultures at Barwon Health and Monash Health, respectively. The main differences observed were in Enterococcus spp., which were cultured in 8.8% and 4.9% of cultures at Barwon Health and Monash Health, respectively, and Candida spp. in 4.2% and 1.5% of cultures at Barwon Health and Monash Health, respectively. The largest differences were found in fluoroquinolone resistance with 12.1% of organisms resistant to ciprofloxacin at Barwon Health compared to 6.4% at Monash Health and 7.1% of organisms resistant to vancomycin compared to 20.1% at Barwon Health and Monash Health, respectively. Conclusion This study demonstrates that there is considerable variability in the uropathogens and their antimicrobial susceptibility profile in two large health services in the same state. We recommend that each centre performs regular analysis of their uropathogen antibiogram to develop local guidelines for treatment and pre‐operative prophylaxis for uropathogens.